Pengaruh Perputaran Kas Dan Perputaran Piutang Terhadap Tingkat Likuiditas Pada PT Citra Batam Millenium - juliana ana (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2020)
Companies that cannot control liquidity can lose the trust of external companies and distributors. Company liquidity can reflect the company’s ability to repay business debt. The main objective of this research is to see whether there is a significant influence between cash turnover and accounts receivable turnover, both partially and simultaneously on the level of liquidity. The sample collection technique uses purposive sampling by determining certain weighted value samples so that the data used have a more representative value and the sample can represent the entire population. In this study using quantitative data in the form of secondary data sources by collecting company report data from 2014 to 2018 in 60 population samples. Researchers used multiple linear regression data analysis methods in order to produce data processing in the form of tables and graphs and conclusions. The results of the SPSS program in study showed partially cash turnover and account receivable turnover there no significant effect on the level of liquidity and the result simultaneous test showed cash turnover and account receivable turnover significant effect the level liquidity.